Design of a 3-RPR Flexure System for Optical Switch Assembly. (26th August 2020) - Kou, Guiyue; Lin, Mouyou; Chu, Changbao
Abstract : In the MEMS optical switch assembly, the collision is likely to happen between the optical fiber and the U-groove of the chip due to the uncontrollable assembly errors. However, these errors can hardly be completely eliminated by the active control using high precision sensors and actuators. It will cause the large acting force and part damage, which further leads to the assembly failure. To solve this question, this paper presents a novel low-cost three-degree-of-freedom (three-DOF) passive flexure system to adaptively eliminate the planar assembly errors. The flexure system adopts three parallel kinematic chains with a novel 3-RPR structure and has a compact size with a diameter of 125 mm and thickness of 12 mm. A novel eddy current damper with the structure of Halbach array permanent magnets (PMs) is utilized to suppress the adverse mechanical vibration of the assembly system from the background disturbances. Analytical models are established to analyze the kinematic, static, and dynamic performances of the system in detail. Finally, finite element analysis is adopted to verify the established models for optimum design. The flexure system can generate a large deformation of 1.02 mm along the two translational directions and 0.02° along the rotational direction below the yield state of the material, and it has much higher natural frequencies than 200 Hz. Moreover, the large damping force means that the designed ECD can suppress the system vibration quickly. The above results indicate the excellent characteristics of the assembly system that will be applied into the optical switch assembly.